Efektivitas ekstrak metanol batang pisang mauli 100%padapenyembuhan luka punggung mencit (Mus musculus)ditinjau dari jumlah sel radang (Effectiveness of 100%extract of Mauli Banana stem to healing process of mice’s (Mus musculus)back from the perspective of the number of inflamed cell) - Maharani Laillyza Apriasari; Amy Nindia Carabelly; Gusti Febby Aprilia (DiscoverSys Inc., 2014)
Banana plant especially its trunk contains many kinds of fitokimia such as saponin, flavonoid, and tannin whichfunction as antibiotic and fasten the healing process. Mauli banana stem extract is often used by the people in HuluSungai Utara Banjarmasin Province to fasten healing skin injury. The purpose of this research is to histopathologicallyexamine the effectiveness of Mauli Banana stem extract to the healing process of the mice’s back (Mus musculus)onthe 3rd day. This purely true experimental research with post test only with control design used 27 mices which weredivided to 3 groups. Treatment group was given methanol extract of mauli banana stem whose average scores ofneutrofil and macrofag are representatively 2.333 and 1; negative control group was given aquadest with its averageneutrofil and macrofag scores are representatively 1.055 dan 1.678; and positive control group was given standardmedicine which contained Aloe veraextract with its average neutrofil and macrofag scores are representatively 1.066dan 1.667. The result of Kruskall-Wallis and Mann-Whiney showed a significant difference between treatment groupand negative control group. It can be concluded that the extract methanol of mauli banana stem on the healing processof injury to mancit’s back histopathologically influences the decreasing acute inflamed (neutrofil) cell and theincreasing chronic inflamed (macrophage) cell on the third day. In this case the extract of mauli banana stem ismedically potential to fasten the healing process of injury.